2003
DOI: 10.1590/s1516-14392003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Superficial modifications in TiO2 and Al2O3 ceramics

Abstract: The properties of hydrophilicity or hydrophobicity of materials are defined mainly, though not exclusively, by their composition, morphology and surface energy. In this work, titanium dioxide (TiO2) and aluminum oxide-alumina (Al2O3) ceramics prepared by uniaxial pressing were studied in terms of surface energy. The surfaces of these ceramics were treated with nitrogen plasma, using a stainless steel reactor excited by a 13,6 MHz radio frequency operating at 50 W input power and 13 Pa nitrogen pressure. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Above Particulate Nanoinsecticides: A New Concept in Insect Pest Management http://dx.doi.org/10.5772/intechopen.72448 the critical value, the capillary forces are the predominant forces [87]. Due to the different contact angles, hydrophilic substances as DE [88,89] are more exposed to the influence of moisture than hydrophobic materials (synthesized Al 2 O 3 ; [90]). In addition, water adsorption also affects the surface energy of the particles [91].…”
Section: Discussionmentioning
confidence: 99%
“…Above Particulate Nanoinsecticides: A New Concept in Insect Pest Management http://dx.doi.org/10.5772/intechopen.72448 the critical value, the capillary forces are the predominant forces [87]. Due to the different contact angles, hydrophilic substances as DE [88,89] are more exposed to the influence of moisture than hydrophobic materials (synthesized Al 2 O 3 ; [90]). In addition, water adsorption also affects the surface energy of the particles [91].…”
Section: Discussionmentioning
confidence: 99%
“…Note that the validity of Washburn in such fine channels (down to 3 µm radius) has been demonstrated with water [19]. The contact angle of water on sintered alumina compacts, θ ls , is 37° [20]. For an assumed tortuosity of τ = 1 the calculated value for truet^ using Equation (2) is 50 ms. For an assumed τ = 5, the truet^ lengthens to 0.86 s and for assumed τ = 10 to 4.5 s. It is, therefore, clear that capillarity through the very fine aligned channels in the membrane is rapid.…”
Section: Resultsmentioning
confidence: 99%
“…Hysteresis was not observed in the 5 nm ␥-alumina membrane (Fig. 5), which may reflect the greater water capacity relative to titania [29]. Non-linear flux behavior and hysteresis was attributed to the presence of physisorbed water on pore surfaces, which led to a reduction in the effective pore diameter.…”
Section: Transport Behavior Of Partially Hydrated Liquid Carbon Dioxidementioning
confidence: 93%
“…This analysis shows that the 1 kDa and 5 kDa titania membranes exhibit the same degree of pore blockage, while that of ␥-alumina is nearly two-fold greater. Comparatively, Santos et al [29] have reported that the water adsorption capacity for ␥-alumina is twice that of titania, which can be attributed to the higher sorption capacity of surface hydroxyl sites on ␥-alumina. These hydroxyl sites can also chemisorb carbon dioxide (discussed in Section 4.3).…”
Section: Transport Behavior Of Dehydrated Liquid Carbon Dioxidementioning
confidence: 97%